The Oxford handbook of dance and wellbeing - Karkou, Vicky; Oliver, Sue; Lycouris, Sophia (Oxford University Press, 2017)
"The Oxford Handbook of Dance and Wellbeing adopts a broad understanding of wellbeing, considering various applications of dance in promoting it. The five sections encompass diverse perspectives on dance and related movement practices, including (i) physical, socio-cultural and emotional aspects, (ii) performance, (iii) education, (iv) community, and (v) dance in health care settings. Within these diverse contexts, theoreticians, scientists, researchers and practitioners from around the world engage, and invited readers to engage, in configuring dance, wellbeing and creative cross-overs"--
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Lebensqualität; Gesundheit; Wohlbefinden; Bewegungstherapie; Tanzerziehung; Tanztherapie; Tanz